Suatu Dilema Identitas Soisal Pada Pemakaian Warna Sepu’ Dalam Upacara Adat di Toraja - Theofilus Welem (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2022)
This research is backgrounded by the fact that the use of the color sepu' as a marker of social identity for the Toraja people is no longer seen from the greatness of a person or a family, its use is also no longer seen where the tongkonan came from or from which descendants came from or were born, but the most important thing is how big a party can be done. The purpose of this study is to see the dilemma of social identity that occurs in the use of sepu' color in the implementation of traditional ceremonies in Toraja. This paper will use Jenkis' theory of social identity to see the dilemma of social identity that occurs. The method used is a qualitative method with a descriptive approach. Data collection was carried out through literature studies and interviews, the results showed that there was a dilemma of wearing colors on sepu' in traditional ceremonial activities in Toraja that occurred from the side of the person who carried out the traditional ceremonial activities, namely from people who had a middle social class and even the lower class (tana' karurung and tana' kua-kua). The conclusion of the social identity dilemma that occurs in the use of the color sepu' is due to the factors of modernity, religious factors and the biggest is because society has experienced economic development so that it has a lot of wealth which in the end irresponsibly uses the color sepu' which should not be used. However, in all the efforts that society tries to make in order to let go of the social strata, the social strata that are actually owned and inherited will not be forgotten.